2022
DOI: 10.1155/2022/6198448
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Data and Biocalculation Methods of GABRD Determine the Clinical Characteristics and Immune Relevance of Colorectal Cancer

Abstract: Background. The aim of this study was to clarify the expression of gamma-aminobutyric acid type A receptor delta subunit (GABRD) gene in pan-cancer and its correlation with patient prognosis, and to investigate the function and possible mechanism of GABRD in colorectal cancer (CRC). Methods. The Cancer Genome Atlas (TCGA) data were used to analyze the expression differences of GABRD in pan-cancer, and the correlation between GABRD and clinical prognosis of various tumors was analyzed by Cox regression method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Analysis of TCGA data has unveiled a notable up-regulation of GABRD across various tumor tissues [43] . This upregulation has been particularly observed in esophageal squamous cell carcinoma, and studies have indicated that its suppression can hinder tumor cell proliferation and migration, underscoring its relevance in tumorigenesis [40] .…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of TCGA data has unveiled a notable up-regulation of GABRD across various tumor tissues [43] . This upregulation has been particularly observed in esophageal squamous cell carcinoma, and studies have indicated that its suppression can hinder tumor cell proliferation and migration, underscoring its relevance in tumorigenesis [40] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the basic physiological process of protein digestion and absorption, which may change cancer, can impact tumor growth and development [ 48 ]. Recent research has identified a correlation between the expression of the GABRD gene in CRC and patient prognosis, suggesting potential involvement with pathways such as protein digestion and absorption, and ECM-receptor interaction [ 49 ]. These findings lend further support to our KEGG analysis results, although the precise mechanisms warrant further experimental validation.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%